Noise and vibrations in machine tools. Issue 2 (2021) - Wegener, Konrad; Bleicher, Friedrich; Heisel, Uwe; Hoffmeister, Hans-Werner; Möhring, Hans-Christian
Abstract: Mechanical manufacturing processes and their production machinery are noisy. The noise always stems from transient forces that excite the structure to vibrations, emitting sound waves into the environment due to vibrations on the surface. Noise emission is today considered as a quality defect of machinery and thus methods and means are sought to mitigate the noise emission to a level compatible with human operators. On the other hand as the noise origin is the process itself, the emitted noise has a signal content that directly indicates the status of the process and sometimes also the health state of the machine and its elements. Noise reduction today is still fairly experience based, which requires generating a good understanding of noise generation, noise transmission and noise radiation and is discussed in this paper. Measurement of noise and its analysis are indispensable for the traceback to the origin to focus the countermeasures but also to reveal the signal content out of the sound waves. Noise prediction is still at the threshold of industrial application, but will in future play a major role for including noise topics into the design from the beginning and not only as corrective measures after the machine is built. Available simulation tools are presented in this paper. The greatest progress in this respect stems from room acoustics and the automotive industry, where the requirements are much stricter than in the manufacturing environment. Ways and achievements in the utilization of noise signals for process and machine health monitoring will also be presented. The industry seeks here for broad band sensors, able to carry large amounts of easy to retrieve signals to reduce the number of additional sensors. Typical standards today collect countermeasures being applied for spreading the knowledge generated for intuitive approaches. The paper also shows future trends and developments and the research required in that field.